(untitled) (The Review of Diabetic Studies, 2025)
Background: Early Childhood Caries (ECC) remains one of the most common chronic diseases affecting children under six years of age and has been consistently linked to impaired Oral Health–Related Quality of Life (OHRQoL). This systematic review aimed to synthesize empirical evidence on how ECC influences the quality of life of preschool children and their families across different cultural and socioeconomic contexts. Methods: A comprehensive search was conducted across PubMed, Scopus, Embase, Web of Science, and Google Scholar up to December 2025, following PRISMA 2020 guidelines. Eleven observational studies were included. Data were extracted on sample characteristics, ECC severity, OHRQoL measures (ECOHIS, SOHO-5, PedsQL), and quantitative outcomes. Results: Across studies, children with ECC consistently reported poorer OHRQoL scores, with severity of caries showing a graded negative association. Pain, functional limitations, and parental distress were the most commonly affected domains. Sociodemographic factors such as low income, limited parental education, and darker skin color exacerbated the impacts. The magnitude of ECC’s influence on OHRQoL was comparable across geographic regions including Latin America, Asia, and the Middle East. Conclusion: ECC significantly diminishes the physical, psychological, and social dimensions of children’s quality of life. These findings highlight the importance of preventive oral health programs and early interventions targeting socially vulnerable groups to reduce ECC-related health disparities.